Effects of Mechanical Stretching on the Properties of Conjugated Polymers: Case Study for MEH‐PPV and P3HT Oligomers. Issue 20 (6th September 2018) - Roldao, Juan Carlos; Batagin‐Neto, Augusto; Lavarda, Francisco Carlos; Sato, Fernando
ABSTRACT: Nowadays, the development of new materials for applications in flexible optoelectronic devices is one of the main frontiers of science. However, in order to improve the applicability and durability of such devices, a deeper understanding of the effects induced by mechanical deformations on the properties of their components is still necessary. In this sense, in the present study, it is evaluated the effect of mechanical stretching in the structural, electronic, and optical responses of two widely investigated organic polymers with great technological interest: poly(2‐methoxy, 5‐(2′‐ethylhexyloxy)‐1, 4‐phenylene vinylene) and poly(3‐hexylthiophene‐2, 5‐diyl). Hartree–Fock and density functional theory electronic structure calculation methods were employed for the study of oligomeric structures subjected to increasing stretch levels along the polymerization axis. The results show a dependence of the polymer properties with the mechanical deformation, allowing to identify distinct response regimes according to the main chain stretching. In particular, it is noticed that large stretches lead to nonfunctional devices, mainly due to the localization of the frontier orbitals and degradation of optoelectronic properties. In addition, it was also identified that very small deformations can lead to some interesting optoelectronic responses, which could indicate an alternative route for the design of organic devices via mechanical processes. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1413–1426 Abstract : A deeper understanding of the effects induced by mechanical deformations on the polymer properties is still necessary to obtain functional flexible devices based on these materials. In this report, the authors evidence the existence of distinct regimes of the polymer properties degradation with the mechanical stretch of the main chains. In general, large stretches lead to nonfunctional devices, mainly due to significant changes induced on the spatial distribution of frontier orbitals. On the other hand, very small deformations can lead to some interesting optoelectronic responses.